2002
DOI: 10.1159/000059632
|View full text |Cite
|
Sign up to set email alerts
|

ICAM-1 Expression on the Surface of T Lymphocytes in Patients with Uveitis: A Comparative Study between the Eye and Peripheral Blood

Abstract: Purpose: We studied the surface expression of intracellular adhesion molecule 1 (ICAM-1) on peripheral and intra-ocular T lymphocytes in patients with active uveitis. Methods: Two-colour flow-cytometric analysis was performed on cells isolated from aqueous humour and peripheral blood of 23 patients with active uveitis and 16 control patients who were to undergo cataract extraction, in order to determine the percentage of cells expressing CD4, CD8 and ICAM-1 (CD54) molecules. Results: In the aqueous humour of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…36 As an intracellular adhesion molecule, ICAM-1 increased the percentage of CD4+ and CD8+ lymphocytes in the aqueous humour of patients with uveitis, compared to control patients. 37 Becker et al have found that treatment with antibodies for ICAM-1 inhibited leucocyte adhesion and infiltration, but not rolling, in murine EIU. 38 Yoshida et al have found that aqueous humour MCP-1 levels were significantly higher in infectious or non-infectious uveitis patients than in controls.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…36 As an intracellular adhesion molecule, ICAM-1 increased the percentage of CD4+ and CD8+ lymphocytes in the aqueous humour of patients with uveitis, compared to control patients. 37 Becker et al have found that treatment with antibodies for ICAM-1 inhibited leucocyte adhesion and infiltration, but not rolling, in murine EIU. 38 Yoshida et al have found that aqueous humour MCP-1 levels were significantly higher in infectious or non-infectious uveitis patients than in controls.…”
Section: Discussionmentioning
confidence: 99%
“…Proinflammatory mediators, such as ICAM‐1, MCP‐1, TNF‐α and IL‐6, are responsible for neutrophil recruitment during inflammation and are crucial intermediaries of ocular inflammation 36 . As an intracellular adhesion molecule, ICAM‐1 increased the percentage of CD4+ and CD8+ lymphocytes in the aqueous humour of patients with uveitis, compared to control patients 37 . Becker et al have found that treatment with antibodies for ICAM‐1 inhibited leucocyte adhesion and infiltration, but not rolling, in murine EIU 38 .…”
Section: Discussionmentioning
confidence: 99%